1998
DOI: 10.1063/1.122354
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced GaN decomposition in H2 near atmospheric pressures

Abstract: GaN decomposition is studied at metallorganic vapor phase epitaxy pressures (i.e., 10–700 Torr) in flowing H2. For temperatures ranging from 850 to 1050 °C, the GaN decomposition rate is accelerated when the H2 pressure is increased above 100 Torr. The Ga desorption rate is found to be independent of pressure, and therefore, does not account for the enhanced GaN decomposition rate. Instead, the excess Ga from the decomposed GaN forms droplets on the surface which, for identical annealing conditions, increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 20 publications
2
58
0
1
Order By: Relevance
“…Liquid Ga droplets were considered to act as a catalyst for GaN decomposition 14 and were found to be correlated with the GaN decomposition enhancement observed in H 2 near atmospheric pressure. 15 Furthermore, given that the absolute value of the GaN decomposition rate approaches the N-limited GaN growth rate ͑i.e., 5.0 nm/min͒ at 810°C, this temperature marks an upper limit for the successful growth of GaN for this fixed nitrogen flux and if exceeded results in thermal etching. It is therefore expected that higher active nitrogen fluxes will increase the Ga incorporation rate and thus enable growth at even higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid Ga droplets were considered to act as a catalyst for GaN decomposition 14 and were found to be correlated with the GaN decomposition enhancement observed in H 2 near atmospheric pressure. 15 Furthermore, given that the absolute value of the GaN decomposition rate approaches the N-limited GaN growth rate ͑i.e., 5.0 nm/min͒ at 810°C, this temperature marks an upper limit for the successful growth of GaN for this fixed nitrogen flux and if exceeded results in thermal etching. It is therefore expected that higher active nitrogen fluxes will increase the Ga incorporation rate and thus enable growth at even higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…For GaN substrates, it was found that the GaN surface is vulnerable to H 2 etching in the MOCVD ambient [52]. A layer-by-layer etching mode is rather difficult to achieve, likely due to large difference of the partial vapor pressure of surface N and Ga atoms [53].…”
Section: Substrate Pretreatmentmentioning
confidence: 99%
“…The differences in prefactors suggests that in addition to overall nucleation density the growth conditions also play an important role in dislocation reduction. Some of these factors may include preventing additional nucleation on the sapphire by increasing the growth pressure to induce higher GaN decomposition rates [6,14] and increasing the smoothness of the starting substrate to produce grains with improved orientation. Using etched mesas and a SiC growth step, SiC surfaces were generated that contained either atomically smooth mesas with no steps or mesa with regular step arrays [15].…”
Section: Correlation Between Nucleation and Dislocation Densitymentioning
confidence: 99%